Olfactory dysfunction after autoimmune encephalitis depending on the antibody type and limbic MRI pathologies - Hänsel, Martin; Schmitz-Peiffer, Henning; Hähner, Antje; Reichmann, Heinz; Schneider, Hauke (Frontiers in Neurology, 2023)
Objective: Patients' olfactory function after autoimmune encephalitis (AE) involving limbic structures may be impaired. This study aimed to characterize olfactory function in patients after autoimmune encephalitides. Methods: A case-control study was performed including 11 AE patients with antibodies against NMDAR (n = 4), GAD (n = 3), VGKC (n = 3) and antibody-negative AE (n = 1) and a control group of 12 patients with pneumococcal meningo-encephalitis (PC). In subgroup analyses, AE patients with and without NMDAR-antibodies were compared. Olfactory function was assessed using the Sniffin Sticks test and the resulting TDI-score (threshold, discrimination, identification). Involvement of limbic structures was evaluated on imaging data (MRI). Statistical analyses were performed to test for correlations of TDI-score and MRI results. Results: The overall olfactory function of the AE-group and the PC-group was comparable (mean TDI 32.0 [CI 27.3-36.7], 32.3 [CI 28.5-36.0)]. The proportions of hyposmic patients were similar compared to the general population. However, AE patients of the non-NMDAR group had significantly lower TDI-scores (28.9 ±6,8) than NMDAR patients (37.4 ±3.5) (p = 0.046) and a significantly lower discrimination capability than the NMDAR patients (9.9 ±2.0 vs. 14.5 ±0.6) (p = 0.002). The non-NMDAR patients had significantly more limbic MRI pathologies (6/7) compared to the NMDAR patients (0/4) (p = 0.015). Furthermore, a correlation between limbic MRI pathologies and worse capability of smelling discrimination was found (p = 0.016, r = -0.704, n = 11). Conclusions: Our results indicate that patients with NMDAR autoimmune encephalitis have normal long term olfactory function. However, patients with non-NMDAR autoimmune encephalitis appear to have a persistently impaired olfactory function, probably mediated by encephalitic damage to limbic structures.